Diversidad y biomasa aérea de especies arbóreas en bosque de terraza media, Puerto Almendra, Loreto, Perú, 2021 - Taza Pérez, Alison Paola (2023)
The objective of the study was to determine the diversity and aerial biomass in the middle terrace forests of Puerto Almendra, Loreto, Peru. All trees with DBH ? 10 cm, existing in two plots of 1.2 ha in the CIEFOR “El Huayo” arboretum, distributed in each plot of the forest, were evaluated with the non-destructive method. He index of the specific wealth of Margalef indicate,that in plot VII it has an index of 16.69 and in plot VIII it reports an index of 15.35, indicating high specific richness of the species; both plots the Simpson dominance index is 0.97, which indicates a high diversity and dominance of the species; the Shannon-Wiener equity index, plot VII shows a high index of 4.05 and VIII shows a low index of 3.96, which indicates that both plots have a high diversity of tree species; Fisher's Alpha index of plot VII shows 37.64 and plot VIII with 33.41 indicates a high diversity. Plots VII and VIII of the middle terrace forest present the highest similarity of 62%; Regarding aerial biomass, plot VII obtained a total of 279,655.44 Kg and plot VIII with 343,866.18 Kg. There is a high storage of biomass in tree species and a high diversity of species. This leads us to relate the complexity of the species in the forest, but also to find the measure of validity in diversity and to get involved in ecosystem services.